2022
DOI: 10.3389/fmolb.2022.841777
|View full text |Cite
|
Sign up to set email alerts
|

Recent Approaches to the Identification of Novel Microtubule-Targeting Agents

Abstract: Microtubules are key components of the eukaryotic cytoskeleton with essential roles in cell division, intercellular transport, cell morphology, motility, and signal transduction. They are composed of protofilaments of heterodimers of α-tubulin and β-tubulin organized as rigid hollow cylinders that can assemble into large and dynamic intracellular structures. Consistent with their involvement in core cellular processes, affecting microtubule assembly results in cytotoxicity and cell death. For these reasons, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 81 publications
(79 reference statements)
0
19
0
Order By: Relevance
“…The allosteric microtubule destabilizers , colchicine, vinblastine, and maytansine were investigated with PB-GABA-Taxol using previously optimized cellular binding conditions (Figure ). Potent allosteric binding affinities were observed for colchicine ( K b = 80 ± 12 nM, α = 0.08), vinblastine ( K b = 7 ± 2 nM, α = 0.18), and maytansine ( K b = 3 ± 1 nM, α = 0.21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The allosteric microtubule destabilizers , colchicine, vinblastine, and maytansine were investigated with PB-GABA-Taxol using previously optimized cellular binding conditions (Figure ). Potent allosteric binding affinities were observed for colchicine ( K b = 80 ± 12 nM, α = 0.08), vinblastine ( K b = 7 ± 2 nM, α = 0.18), and maytansine ( K b = 3 ± 1 nM, α = 0.21).…”
Section: Resultsmentioning
confidence: 99%
“…This class of compounds includes FDA-approved microtubule stabilizers such as taxanes and epothilones and microtubule destabilizers such as colchicine, vinblastine, and maytansinoids, which are delivered as antibody–drug conjugates (Figure ). The mechanism of action of taxane drugs involves the engagement of a 3.5 Å hydrophobic cleft of the protein β-tubulin when it heterodimerizes with α-tubulin to form tubular protein assemblies. , Binding of taxanes to polymerized microtubules is favored, and this binding induces conformational changes to microtubules that lower the critical concentration required for their assembly of these structures. In contrast, destabilizers such as vinblastine weaken microtubule lattices, whereas colchicine inhibits the growth of microtubules by preventing conformational changes of dimers of α- and β-tubulin required for their polymerization . Although microtubule-targeting drugs are effective first- and second-line therapies for numerous cancers, novel agents that bind microtubules are of substantial interest due to the emergence of drug resistance, the lack of efficacy for some cancers, and the complexity associated with the syntheses of some of these compounds. Furthermore, dose-limiting side effects such as peripheral neuropathy associated with taxanes, epothilones, and their delivery vehicles continues to drive the discovery of novel agents with greater bioavailability and improved therapeutic windows. Resistance to these drugs can be mediated by several mechanisms, including the overexpression of drug efflux transporters such as p -glycoprotein (MDR1), mutations in β-tubulin, and the expression of antiapoptotic proteins such as survivin. …”
Section: Introductionmentioning
confidence: 99%
“…30 These properties are appealing for photopharmacology, which aims at controlling drug action on demand at selected locations using light, to enable precise responses and reduce unwanted side effects of treatments, or to manipulate specific cell types and neural circuits for investigational purposes. 31,32 Many photoswitchable bioactive molecules have been reported that offer high pharmacological specificity and potency for a diversity of targets, including ion channels, 33−36 G protein-coupled receptors, 37−39 protein−protein interactions, 40,41 and enzymes. 42−45 Most are based on aryl azo compounds, 46−48 which are difficult to isomerize using orange−red light without introducing substituents that often perturb the pharmacological properties of the original compound.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The hurdles to operate DASAs in aqueous solutions are most aggravating since they are native red/NIR-absorbing, negative photochromic compounds that would afford low scattering and deep penetration in tissue without incurring phototoxicity in biological applications . These properties are appealing for photopharmacology, which aims at controlling drug action on demand at selected locations using light, to enable precise responses and reduce unwanted side effects of treatments, or to manipulate specific cell types and neural circuits for investigational purposes. , Many photoswitchable bioactive molecules have been reported that offer high pharmacological specificity and potency for a diversity of targets, including ion channels, G protein-coupled receptors, protein–protein interactions, , and enzymes. Most are based on aryl azo compounds, which are difficult to isomerize using orange–red light without introducing substituents that often perturb the pharmacological properties of the original compound. Photoswitching with continuous NIR light has been achieved in diazocines and using two-photon (2P) excitation of simple azobenzenes ,, in neurons, but the latter requires pulsed lasers and precision optics. , Thus, developing compounds that can be directly photoswitched in vivo with continuous-wave red or NIR light using portable devices (e.g., LEDs) remains an unmet need in basic and applied photopharmacology. They would enable noninvasive drug-based phototherapies and facilitate their translation to the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules are among the most important molecular targets for cancer chemotherapeutic treatment [1][2][3]. The formation of microtubules is a dynamic process that involves the assembly and disassembly of α and β-tubulin subunits [4][5][6].…”
Section: Introductionmentioning
confidence: 99%